Fermentative biohydrogen and biomethane co-production from mixture of food waste and sewage sludge: Effects of physiochemical properties and mix ratios on fermentation performance. (15th December 2016) - Cheng, Jun; Ding, Lingkan; Lin, Richen; Yue, Liangchen; Liu, Jianzhong; Zhou, Junhu; Cen, Kefa
Highlights: Microanalyses revealed food waste had more gelatinized organics and less mineral ash. Mixed food waste and sewage sludge at 5 ratios were used for H2 and CH4 co-production. Highest H2 yield of 174.6 mL/gVS was achieved when food waste:sewage sludge was 3:1. Co-fermentation enhanced carbon conversion by strengthening hydrolysis of substrates. Energy yield rose from 1.9 kJ/gVS in H2 to 11.3 kJ/gVS in H2 and CH4 co-production. Abstract: The accumulation of increasingly generated food waste and sewage sludge is currently a heavy burden on environment in China. In this study, the physiochemical properties of food waste and sewage sludge were identified using scanning electron microscopy and Fourier transform infrared spectroscopy to investigate the effects on the fermentation performance in the co-fermentation of food waste and sewage sludge for biohydrogen production. The high gelatinized organic components in food waste, the enhanced bioaccessibility due to the dilution of mineral compounds in sewage sludge, and the balanced C/N ratio synergistically improved the fermentative biohydrogen production through the co-fermentation of food waste and sewage sludge at a volatile solids (VS) mix ratio of 3:1. The biohydrogen yield of 174.6 mL/gVS was 49.9% higher than the weighted average calculated from mono-fermentation of food waste and sewage sludge. Co-fermentation also strengthened the hydrolysis and acidogenesis of the mixture, resulting in a total carbon conversion efficiency of 63.3% and an energy conversion efficiency of 56.6% during biohydrogen production. After the second-stage anaerobic digestion of hydrogenogenic effluent, the energy yield from the mixed food waste and sewage sludge significantly increased from 1.9 kJ/gVS in the first-stage biohydrogen production to 11.3 kJ/gVS in the two-stage fermentative biohydrogen and biomethane co-production.